Characterization of CNT and It's carrier mobility dependency on diameter in Back-Gated CNT-FET. (2021) - Pavan Kalyan, GV.; Sarkar, Argha; Aswini, C; Chakraborty, Pinaki
Abstract: Based on the chiral indices, different structures like an arm chair, zigzag and chiral are formed and carbon nanotube (CNT) shows semiconducting and metallic properties. This is a very interesting phenomenon in the field of nanoelectronics research. Some fundamental parameters like diameter, bandgap, number of hexagons in a unit cell, and temperature affect the carbon nanotube properties. These parameters may also change the carrier mobility in the carbon nanotube based back-gated field effect transistor (FET). Diameter (directly proportional with mobility) and temperature (inversely proportional to the mobility) dependency is very much important on charge density.